A framework for the analysis of gender, intra-household dynamics, and livestock disease control with examples from Uasin Gishu District, Kenya - Curry, J.; Huss-Ashmore, R.; Perry, Brian D.; Mukhebi, A.W. (Springer, 1996)
As livestock disease control programs in Africa begin to rely more upon para-professionals and livestock producers as deliverers of animal health care services, understanding the role different household members play in providing animal health care becomes increasingly important. This paper presents a framework for the analysis of gender aspects of livestock disease control based on a similar framework developed by Feldstein and Poats (1989). The utility of this framework is illustrated using household-level data collected from a district in central Kenya. Adult women and elderly men in the sample have primary responsibility for livestock care, and are therefore well placed to diagnose illness. Dipping and spraying of animals to prevent tick-home and other diseases is the primary responsibility of adult males. Decisions regarding use of milk from the morning milking are more likely to be made by adult men. It is morning milk that is most often sold. Adult women, however, make decisions about use of evening milk, which is most often kept for household consumption. Knowledge of livestock diseases did not appear to vary significantly by gender, although some elderly men did possess extensive knowledge of indigenous disease categories and traditional remedies. The importance of recognizing gender issues in planning and implementing livestock disease control programs is discussed.